Natural convection in wavy enclosures with volumetric heat sources - Öztop, Hakan Fehmi; Abu-Nada, Eiyad; Varol, Yasin; Chamkha, Ali (Elsevier France-Editions Scientifiques Medicales Elsevier, 2011)
In this paper, the effects of volumetric heat sources on natural convection heat transfer and flow structures in a wavy-walled enclosure are studied numerically. The governing differential equations are solved by an accurate finite-volume method. The vertical walls of enclosure are assumed to be heated differentially whereas the two wavy walls (top and bottom) are kept adiabatic. The effective governing parameters for this problem are the internal and external Rayleigh numbers and the amplitude of wavy walls. It is found that both the function of wavy wall and the ratio of internal Rayleigh number (Ra(l)) to external Rayleigh number (Ra(E)) affect the heat transfer and fluid flow significantly. The heat transfer is predicted to be a decreasing function of waviness of the top and bottom walls in case of (Ra(l)/Ra(E))> 1 and (Ra(l)/Ra(E)) < 1. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Natural convection; Volumetric heat generation; Wavy enclosure